Christian Education Perspective of Senguyun Tradition in Dayak Kenyah Bakung Tribe - Mary, Eirene; Udau, Samuel (Didache: Journal of Christian Education, 2025)
Gotong royong is an important Indonesian value, meaning working together. This kind of working together is also found in Dayak Kenyah Tribe in Indonesia.  One form of working together is senguyun. Senguyun is a voluntary work group composed of any number of men and youths who feel that they can effectifely join forces for mutual benefit. This practice has been implemented by the Dayak Kenyah tribe before christianity entered and continues to be carried out to this day. This article aims to reveal the value of senguyun as part of the tribe’s local wisdom, and as a way for Christian education for nurturing the faith of church members. The method used in  this research is a descriptive qualitative method. Data collection techniques employed are observation, interviews and document analysis. The result of the study shows that senguyun is a form of local wisdom that is in accordance with bibilical principles and should be regarded as a noble cultural heritage that must continue to be preserved.